Effectiveness and failures of a fast track protocol after cytoreduction and hyperthermic intraoperative intraperitoneal chemotherapy in patients with peritoneal surface malignancies. (December 2016) - Cascales-Campos, P.A.; Sánchez-Fuentes, P.A.; Gil, J.; Gil, E.; López-López, V.; Rodriguez Gomez-Hidalgo, N.; Fuentes, D.; Parrilla, P.
Abstract: Background: The aim of this study was to analyze the results short term perioperative of patients with peritoneal surface malignancies undergoing cytoreduction with peritonectomy and HIPEC under a controlled fast track protocol and evaluate the factors related to the failure of implementation of the protocol. Patients and method: We prospectively analyzed a consecutive series of patients (N = 156) with peritoneal surface malignancies treated by cytoreductive surgery with peritonectomy procedures and HIPEC from September 2008 until December 2014, in whom a fast track protocol was implemented. We limited the protocol to patients who had optimal cytoreduction, HIPEC administration, and not more than one digestive anastomosis. All patients signed informed consent for surgery and the perioperative multimodal recovery program. Results: A total of 156 consecutive patients, with a median age of 57 years were included in the study. Median PCI was 8 (IQR: 0–32). Morbidity rate (Clavien-Dindo) was 25.6%, with a major morbidity rate (Clavien-Dindo III-IV) of 11.5%. One hundred and three patients (66%) completed the protocol. Multivariate analysis identified the following independent factors, which were related to failure of the protocol: age over 57 years (OR = 3.159, 95% CI: 1.286–7.758, p < 0.05), the realization of a digestive anastomosis (OR = 3.834, 95% CI: 1.562–9.414, p < 0.005) and occurrence of postoperative complications (OR = 18.704, 95% CI: 6.888–50.790, p < 0.001) Conclusions: Our data support the idea that in selected patients undergoing cytoreductive surgery and HIPEC, with a low PCI and especially no necessity to perform a digestive anastomosis, the implementation of a fast track program is feasible. Highlights: FT is feasible in cytoreductive surgery and HIPEC, without digestive anastomosis. FT achieves high compliance rates and shorter postoperative recovery staying. FT does not increase rates of postoperative morbidity or readmission.